2017
DOI: 10.3389/fpls.2017.01618
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Reserve Pools in Two Miscanthus × giganteus Genotypes under Contrasting N Managements

Abstract: Nitrogen (N) reserves in vegetative tissues contribute N to regrowth of Miscanthus × giganteus shoots in spring, but our understanding of how N fertilization and plant genotype affect this process is incomplete. Our specific objectives were to: (1) determine how N fertilizer management impacts accumulation of dry matter and N among aboveground and belowground tissues and organs; (2) understand how changes in N management and tissue N concentration influence seasonal fluctuations in concentrations of buffer-sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Perhaps the poorer performance of ‘Illinois’ in Iowa indicates lower tolerance to the cooler growing conditions at that site relative to temperatures of Virginia. Dierking et al () also reported a reduction in the growth rate of both shoot and stembase biomass from August through November for ‘Illinois’ in cooler Indiana, USA, but not for an open pollinated tetraploid sibling of ‘Nagara’. Freedom's biomass yields were intermediate to these cultivars both in Virginia and in Iowa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the poorer performance of ‘Illinois’ in Iowa indicates lower tolerance to the cooler growing conditions at that site relative to temperatures of Virginia. Dierking et al () also reported a reduction in the growth rate of both shoot and stembase biomass from August through November for ‘Illinois’ in cooler Indiana, USA, but not for an open pollinated tetraploid sibling of ‘Nagara’. Freedom's biomass yields were intermediate to these cultivars both in Virginia and in Iowa.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘Illinois’ clone is an unlicensed public cultivar obtained in 1988 from the Chicago Botanic Garden as a sterile triploid. ‘Illinois’ is the most common M. ×giganteus cultivar utilized for research and commercial purposes in the United States and Europe (Dierking, Allen, Cunningham, Brouder, & Volonec, ; Głowacka et al, ). ‘Freedom’ M. ×giganteus, the commercial name of the patented MSU‐MFL1 (Baldwin, ), has recently been found to have identical multilocus cultivars and no nuclear or cytoplasmic genetic differences compared with ‘Illinois’ (Głowacka et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general fertilizer requirement of maize grown for forage and for grain are the same as that for a biomass crop. N requirements differ greatly for forage crops, and legumes and rhizome crops like Miscanthus have low N requirements ( Dierking et al, 2017 ). Improving NUE using transporter marker genes as indicators of the crop status in the field could be valuable ( Fan et al, 2017 ).…”
Section: Improving Forage Cropsmentioning
confidence: 99%
“…Specific vegetative storage proteins (VSPs) are deposited in late-season taproots of alfalfa (Medicago sativa L.) and white clover (Trifolium repens L.) [65,66] to support regrowth in spring. Non-VSPs N resources formed in red clover (T. pratense L.) and other perennial forage legumes are depleted prior to the next growing season [67,68].…”
Section: Turnover Of Organics and Minerals In The Goldenrod Colonymentioning
confidence: 99%